1997
DOI: 10.1021/je960350u
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Studies on the Binary Complexes ofN-[Tris(hydroxymethyl)methyl]glycine with Th4+, Ce3+, La3+, and UO22+and Medium Effects on a Th−Tricine Binary Complex

Abstract: The stability constants for M n+ -tricine binary complexes (1:1 and 1:2), where M n+ ) Th 4+ , Ce 3+ , La 3+ , and UO 2 2+ , have been determined pH-metrically in aqueous media at 25 °C and in the presence of 0.10 mol dm -3 (KNO 3 ). The binary Th-tricine (1:1) complex was studied in the presence of different organic solvents as well as in the presence of different ratios of dioxane and at different temperatures. The calculated stability constants have been discussed in terms of the nature of both the metal io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…The complexation of Tris with La, Ce and Th was studied by El-Roudi and co-workers. 68 El-Gahami et al 69,70 studied the complexation of MES and MOPSO with dibutyltin(IV) and dimethyltin(IV) cations. essentially eliminated in Tris buffer.…”
Section: Complexation Studies Between Good'sbuffers and Lanthanides Amentioning
confidence: 99%
“…The complexation of Tris with La, Ce and Th was studied by El-Roudi and co-workers. 68 El-Gahami et al 69,70 studied the complexation of MES and MOPSO with dibutyltin(IV) and dimethyltin(IV) cations. essentially eliminated in Tris buffer.…”
Section: Complexation Studies Between Good'sbuffers and Lanthanides Amentioning
confidence: 99%
“…Although the two ligands H 2 L 1 and H 2 L 2 have a comparable basicity (pK a2 8.20 and 8.25 for H 2 L 1 and H 2 L 2 , respectively [17,48] ) the stability of the 1:1 binary metal complex of H 2 L 1 is higher than that of the corresponding binary complex of H 2 L 2 . This behavior can likely be ascribed to The 1:1:1 ternary complex containing H 2 L 2 is more stable than the corresponding one containing H 2 L 1 ligand.…”
Section: Formation Constant Valuesmentioning
confidence: 99%
“…The electronic spectra of the Fe 3+ and Cu 2+ chelates (Figures 11 and S3) were carried out in Nujol mull. The results of the Fe 3+ spectrum shows five bands at 27800, 23700, 20600, 18700 and 17400 cm −1 assignable to 6…”
Section: Electronic Spectra and Magnetic Measurementsmentioning
confidence: 97%
“…Also, it was used in animal tissue culture . Several studies of tricine with metal ions were reported by complexometric , potentiometric , cyclic voltammetry and polarography methods . Tricine ( L 1 ) acts as an expellant chelating agent forming uni‐, bi‐ and/or tridentate manners via soft donor atoms (carboxylate oxygen, amido nitrogen and alcoholic oxygen groups).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation